2018
DOI: 10.5897/ajest2017.2454
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of water quality in the lower Nyong estuary (Cameroon, Atlantic Coast) from environmental variables and phytoplankton communities composition

Abstract: The aim of this study was to provide a first-hand water quality assessment of the River Nyong estuary, Southern Atlantic coast of Cameroon. Environmental variables and phytoplankton communities were monitored at four surface stations in the estuary for 2 season cycles from 2014 to 2015. A total of 208 species of phytoplankton, belonging to five (5) groups of microalgae, were identified. The ShannonWeaver diversity index showed a qualitative seasonal difference in composition of the phytoplankton community. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
(19 reference statements)
3
12
0
Order By: Relevance
“…Our study found high correlations between phytoplankton diversity indices and environmental variables of nutrients and nutrient ratios in the Jiulong River estuary, indicating that nutrients and nutrient ratios contributed significantly to phytoplankton biodiversity patterns, which is in agreement with findings from previous studies conducted in similar estuarine environments (Schoor et al, 2008;Li et al, 2010;Huang et al, 2013;Chu et al, 2014;Zhang et al, 2015;Anselme et al, 2018). The relative contribution was quantified by calculating the percentage of the absolute coefficient value of all relevant variables that yielded a statistically significant value (p < 0.001) from optimal regression equations (see Figures 9, 10).…”
Section: Roles Of Nutrients and Nutrient Ratios In Shaping Phytoplank...supporting
confidence: 92%
“…Our study found high correlations between phytoplankton diversity indices and environmental variables of nutrients and nutrient ratios in the Jiulong River estuary, indicating that nutrients and nutrient ratios contributed significantly to phytoplankton biodiversity patterns, which is in agreement with findings from previous studies conducted in similar estuarine environments (Schoor et al, 2008;Li et al, 2010;Huang et al, 2013;Chu et al, 2014;Zhang et al, 2015;Anselme et al, 2018). The relative contribution was quantified by calculating the percentage of the absolute coefficient value of all relevant variables that yielded a statistically significant value (p < 0.001) from optimal regression equations (see Figures 9, 10).…”
Section: Roles Of Nutrients and Nutrient Ratios In Shaping Phytoplank...supporting
confidence: 92%
“…The Nyong estuary is part of the Campo-Nyong hydrosystem of the Atlantic Meridional Coast of Cameroon. Unlike rivers located in the North coast and like all rivers located in Cameroon's South Atlantic the Nyong river like is less watered and subject to an equatorial climate with four seasons which are the long rainy season (LRS), short rainy season (SRS), the long dry season (LDS) and short dry season (SDS) [15] [29] [36]. Climate is influenced by Southwest monsoon, limited on average speed to 10km/h because of the highly developed rainforest [29].…”
Section: Study Area and Sampling Stationsmentioning
confidence: 99%
“…During water quality monitoring, it is very important to assess the physicochemical parameters of water in space and time. Biogeochemical variables and biotics data are usually gathered; several techniques have already been implemented to analyze water quality data, such as data reduction techniques [7] [8] [9] [10] [11], water quality index (WQI) [12] [13] [14] [15], univariate data analysis method, and estuary health index (EHI) [16]. Data reduction techniques usual-ly used to simplify the process of interpreting large datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very few studies specific to water quality in these environments have been carried out despite all the services provided. Existing information concerns the quantitative approach to biodegradation in the freshwater-saltwater mixing zone in the Sanaga and Nyong estuaries, and in the rivers of the Douala Bay (Giresse & Cahet 1997;Fonge et al 2013;Mama et al 2018;Mama et al 2021).…”
Section: Introductionmentioning
confidence: 99%